Investigating the Sephardic Jewish ancestry of colonial French Canadians through genetic and historical evidence - Elizabeth Hirschman (IDEA PUBLISHERS, 2021)
The Spanish Inquisition in 1492 resulted in the deaths of thousands of Spanish Jews and the exile of around 150,000. The Huguenots and Acadians who settled in Colonial French Canada are assumed to be of Christian faith and ancestry. To support this hypothesis, the researcher uses a novel combination of methods drawn from historical records and artifacts, genealogies and DNA testing. In recent years, this combination of methods has led to the discovery that several of the Plymouth Colony settlers, Central Appalachian Colonial settlers, and Roanoke Colony settlers were of Sephardic Jewish origin. Thus, using the new methodology of ancestral DNA tracing, the researcher document that the majority of Huguenot and Acadian colonists in French Canada were of Sephardic Jewish ancestry.  They are most likely descended from Sephardic Jews who fled to France from the Iberian Peninsula in the late 1300s and early 1500s. The researcher additionally propose that some members of both groups continued to practice Judaism in the new world, thus becoming secret Jews or crypto-Jews. The researcher also finds evidence of Ashkenazi Jewish ancestry in both groups.